Lesion with blue bone-a case report - Ilias, Laila Mohamed; Mohammed, Babitha Alingal; PS, Roshini; Ponniah, Anupama; Vijayan, Poornima (Journal of Pathology of Nepal, 2018)
Bizzare parosteal osteochondromatous proliferation, or Nora‘s lesion is a unique bone lesion that most often arises in the small bones of hands and feet. It is characterised by proliferation of chondroid, bony and fibrous tissue, and is occasionally misdiagnosed as a malignant process. Our case was a 31 yr old lady, who presented with a painless swelling near the 5th metacarpal bone of right hand. X-ray showed well marginated mineralised mass arising from the cortical surface of the metacarpal bone. Histopathological examination revealed bizarre parosteal osteochondromatous proliferation composed of varying amounts of cartilage, bone and spindle cells. Cartilage was hypercellular and chondrocytes were enlarged. Ossification was irregular and had a peculiar blue tinctorial quality.